Associations Between OJ Consumption and Dietary and Lifestyle Characteristics and Anthropometric Parameters in a Cross-Sectional Study of U.S. Children from GUTS I and II (P18-007-19). (13th June 2019) - Sakaki, Junichi; Melough, Melissa; Li, Jing; Tamimi, Rulla; Chavarro, Jorge; Chen, Ming-hui; Chun, Ock K
Abstract: Objectives: Concerns about orange juice's (OJ) high sugar content have contributed to reduced consumption in the U.S. The objective of this study is to evaluate the association between 100% OJ consumption and anthropometric indicators and health-related behaviors in adolescents. Methods: Data from the Growing Up Today Study (GUTS), an ongoing prospective cohort study of adolescents from across the U.S. which began its first cohort (GUTS I) in 1996 and its second cohort (GUTS II) in 2004, were analyzed. Results: In a cross-sectional examination of baseline data ( n  = 26, 503), there was a significant trend toward lower prevalence of overweight and obesity among children who reported consuming more OJ among boys of GUTS I and girls and boys of GUTS II. Across each cohort and gender, OJ intake was positively associated with height, height-for-age z-score, total energy intake, consumption of fruits and non-starchy vegetables, consumption of foods of low nutritional quality, and physical activity, while screen time was negatively associated with OJ consumption. In boys across both cohorts, the adjusted odds ratios (OR & 95% CI) of being classified as overweight or obese were 0.90 (0.76, 1.08) for 1–3 glasses of OJ per month, 0.94 (0.80, 1.11) for 1–6 glasses per week, 1.01 (0.82, 1.24) for 1 glass per day, and 1.13 (0.87, 1.48) for >1 glass per day ( P -trend = 0.3251), using non-consumers as a reference. In girls, the ORs were 0.87 (0.74, 1.30) for 1–3 glasses per month, 0.97 (0.83, 1.14) for 1–6 glasses per week, 1.04 (0.84, 1.28) for 1 glass per day, and 0.68 (0.52, 0.89) for >1 glass per day ( P -trend = 0.4345). Conclusions: The results indicate that children consuming more OJ tended to practice healthier dietary and lifestyle habits than OJ non-consumers. Additionally, a lower prevalence of overweight and obesity was observed among children who consumed more OJ. In adjusted analyses controlling for other obesity risk factors, OJ consumption was not associated with higher odds of being overweight or obese. Funding Sources: The Florida Department of Citrus, an executive agency of the state of Florida, provided funding for this project.